PEMBERDAYAAN EKONOMI JAMA’AH MASJID MELALUI KOPERASI - Muhammad Fadlullah; M. Amir Mahmud (LP2M Universitas Ibrahimy, 2017)
This writing discusses about the way of devotion in Mosque Nurul Hidayah Sarimulyo Village Cluring of Banyuwangi. Action of Emphasis devotion is empowerment programmer, implementation of empowerment programmer and result of empowerment program to pilgrim of Nurul Hidayah Mosque. The empowerment is part of participation devotion which put community position as perpetrators of social change has hope by them. The effort will be achieved on two stages for four months and be start from on September until on December 2016. Some cycles are part of empowerment strategic which will do in this devotion. Results of devotion are 1) Form empowerments pilgrim in Mosque are enhancement economic programmer such as training and establishment of cooperation. 2) Implementations of empowerment pilgrim mosque as training and establishment are smoothly. It was formed stewardship and membership on business field such as provision of basic foods, snacks, books of Qiroati, electrical token listrik, PLN and others. But some of them did not yet done because of limited of modal and time. 3) Results of empowerment pilgrim mosque can dug, push and give motivation and make pilgrims independent and confidence.